TimeshareManagement:TheKey IssuesofHospitalityManagers - Kaufmann, Tammie (Elsevier, 2012)
Vacation ownership is becoming a mainstream travel product. Continued growth based on number of units sold and an increasing number of international brands has placed this segment in a very strong position.